Molecular Landscape and Association With Crohn Disease of Poorly Cohesive Carcinomas of the Nonampullary Small Bowel. Issue 4 (22nd February 2023) - Tedaldi, Gianluca; Guerini, Camilla; Angeli, Davide; Furlan, Daniela; Libera, Laura; Lenti, Marco Vincenzo; Grillo, Federica; Fassan, Matteo; Solcia, Enrico; Sessa, Fausto; Paulli, Marco; Di Sabatino, Antonio; et al.
Abstract: Objectives: Poorly cohesive carcinomas (PCCs) are neoplasms defined by a predominantly dyshesive growth pattern with single cell or cord-like stromal infiltration. The distinctive clinicopathologic and prognostic features of small bowel PCCs (SB-PCCs) in comparison with conventional-type small intestinal adenocarcinomas have only recently been characterized. However, as SB-PCCs' genetic profile is still unknown, we aimed to analyze the molecular landscape of SB-PCCs. Methods: A next-generation sequencing analysis through Trusight Oncology 500 on a series of 15 nonampullary SB-PCCs was performed. Results: The most frequently found gene alterations were TP53 (53%) and RHOA (13%) mutations and KRAS amplification (13%), whereas KRAS, BRAF, and PIK3CA mutations were not identified. Most SB-PCCs (80%) were associated with Crohn disease, including both RHOA -mutated SB-PCCs, which featured a non-SRC-type histology, and showed a peculiar appendiceal-type, low-grade goblet cell adenocarcinoma (GCA)–like component. Rarely, SB-PCCs showed high microsatellite instability, mutations in IDH1 and ERBB 2 genes, or FGFR2 amplification (one case each), which are established or promising therapeutic targets in such aggressive cancers. Conclusions: SB-PCCs may harbor RHOA mutations, which are reminiscent of the diffuse subtype of gastric cancers or appendiceal GCAs, while KRAS and PIK3CA mutations, commonly involved in colorectal and small bowel adenocarcinomas, are not typical of such cancers.